Strategi Pengembangan Pariwisata Desa Batununggul Kecamatan Nusa Penida Kabupaten Klungkung Bali - Alicia, Destiny; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA, 2022)
Batununggul Village is the administrative center of the Nusa Penida District. Almost all economic and transportation activities are found in this village. Ease of accessibility, as the center of government, plus its tourist attraction, Nusa Penida has the potential to increase the number of tourist visits. Thus, the researcher is interested in raising the topic of research on the tourism strategy of developing Batununggul Village, Nusa Penida District, Klungkung Regency, Bali. The concept used as the basis in this research is strategy, tourism development, tourism potential, tourist attraction, tourism industry. The method used is a qualitative research method with qualitative data analysis techniques and SWOT data analysis. The types of data used are qualitative and quantitative. Sources of data used are primary data and secondary data. The data was collected through observation, interviews, documentation. The technique of determining informants in this research uses purposive sampling technique. The results of this study indicate that Batungul Village has tourism potential which is divided into 4 components, i.e. attractions that can attract tourist visits. Amenities are all kinds of facilities and infrastructure needed by tourists while in tourist destinations. Accessibility, namely transportation services, is an important access in tourism. Transportation makes it easy to move from one area to another. Additional services are things that must be provided by an agency/local government of a tourist destination, both for tourists and for tourism actors, amenities, accessibility and additional services. Based on these components, it can be seen that the development strategy of Batununggul Village includes the SO strategy, namely aggressively promoting through social media, the ST strategy, which is to provide a unique experience that can make tourists stay longer in Batununggul village, the WO strategy, which is to provide guidance and training to village officials, local communities and teruna teruni to develop Batununggul Village. WT's strategy is to develop marine tourism and utilize technology as a promotional medium. Keyword: Strategy, Development.